Persamaan Operasional Dalam Proses Laminasi Bahan Kemasan - Zafriana, Lusi (Jurnal Teknik Industri, 2011)
Plastick sheet coated like paper for food, bag packaged plastic, etc now is needed for industry. To find material it laminated, it form still in coated laminated process with plastic film. An operational equation in the laminated process need to be founded so that its laminated process can be adjusted with the assigned order. That is usually problem that is not be solved by producers. By using mass balanced principles, the equation can be founded. By using data collected, we can calculate constanta of the equation and also RPM display value that will be used to determine thick of coated film needed for the width film as ordered.